2001
DOI: 10.1002/neu.1072
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of neuropeptide expression, transport, and exocytosis in Drosophila melanogaster

Abstract: Neuropeptides affect an extremely diverse set of physiological processes. Neuropeptides are often coreleased with neurotransmitters but, unlike neurotransmitters, the neuropeptide target cells may be distant from the site(s) of secretion. Thus, it is often difficult to measure the amount of neuropeptide release in vivo by electrophysiological methods. Here we establish an in vivo system for studying the developmental expression, processing, transport, and release of neuropeptides. A GFP-tagged atrial natriuret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 50 publications
11
128
0
Order By: Relevance
“…Muscle 6/7 synapse type Ib boutons were studied in Figs. 1-3 with elav-GAL4 UAS-Anf-GFP larvae (19). Type III boutons were studied in upstream activating sequence (UAS)-Anf-GFP; ccap-GAL4 larvae.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle 6/7 synapse type Ib boutons were studied in Figs. 1-3 with elav-GAL4 UAS-Anf-GFP larvae (19). Type III boutons were studied in upstream activating sequence (UAS)-Anf-GFP; ccap-GAL4 larvae.…”
Section: Methodsmentioning
confidence: 99%
“…driven by a panneuronal driver shows greater accumulation of neuropeptide in Drosophila type III boutons on muscle 12 than in type Ib boutons of the muscle 6/7 synapse (19). Panneuronal expression is not convenient for studying type III boutons, however, because of the presence of closely apposed type Ib, Is, and II boutons, which arise from different neurons.…”
Section: Significancementioning
confidence: 99%
“…Indeed, when we blocked neuropeptide processing through Amon function, or neuropeptide release by reducing Caps, which is required for dense core vesicle release 58 , we could fully suppress the tll knockdown-induced aggression response. Finally, we used a heterologous neuropeptide GFP reporter 59 to visualize the effect of tll knockdown on neuropeptide release from PI neurons and showed that the reporter nearly completely vanishes from PI neurons when tll is knocked down. The identity of the specific neuropeptide(s) that regulate aggression through this transcriptional module is currently not known.…”
Section: Article Nature Communications | Doi: 101038/ncomms4177mentioning
confidence: 99%
“…The UAS-AMPK transgenes were reported previously : UAS-snf1A K57A [Bloomington Stock (BL) # 32112], UAS-snf1A (BL# 32108), UAS-snf1A-RNAi (BL# 32371), and UAS-snf4-RNAi (BL# 34726). Other stocks used in this study were the AKH-GAL4 (BL # 25683) (Lee and Park 2004), UAS-TeTX (BL# 28839) (Sweeney et al 1995), UAS-AKH-RNAi (BL#34960), UAS-rpr (BL# 5823), GAL80 (BL#7018) (McGuire et al 2003), UAS-GCaMP (BL# 32236), and UAS-ANF-GFP (BL# 7001) (Rao et al 2001), all procured from the Bloomington Stock Center (Table 1). The AKHR 01 and AKHR rev lines were kind gifts from Ronald Kuhnlein (Gronke et al 2007).…”
Section: Drosophila Stock and Husbandrymentioning
confidence: 99%